2011
DOI: 10.1158/0008-5472.can-11-0329
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency in the Prometastasis Kiss1 Receptor Gpr54 Delays Breast Tumor Initiation, Progression, and Lung Metastasis

Abstract: Activation of KISS1 receptor (KISS1R or GPR54) by its ligands (kisspeptins) regulates a diverse function both in normal physiology and pathophysiology. In cancer, KISS1-induced KISS1R signaling is known to inhibit tumor angiogenesis and metastasis. However, roles of KISS1 and KISS1R in earlier stages of tumor progression and metastasis in vivo are still unknown. In this study, we demonstrate a critical role for Kiss1r in early stages of tumor progression using mouse tumor models. PyMT/Kiss1r mice with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 45 publications
(65 reference statements)
3
36
0
1
Order By: Relevance
“…In 3D Matrigel cultures of MCF10A cells, we found that exogenous and endogenous KISS1R in exhibited a similar localization pattern at the cell surface membranes and intracellularly ( Figure 1D). This localization was consistent with what was previously reported for KISS1R in MCF10A cells (30).…”
Section: Kiss1r Stimulates Invasion Of Nonmalignant Mammary Epitheliasupporting
confidence: 93%
See 2 more Smart Citations
“…In 3D Matrigel cultures of MCF10A cells, we found that exogenous and endogenous KISS1R in exhibited a similar localization pattern at the cell surface membranes and intracellularly ( Figure 1D). This localization was consistent with what was previously reported for KISS1R in MCF10A cells (30).…”
Section: Kiss1r Stimulates Invasion Of Nonmalignant Mammary Epitheliasupporting
confidence: 93%
“…Using a Kiss1r heterozygous (Kiss1r ϩ/Ϫ ) mouse model and mouse mammary tumor virus-polyoma virus middle T antigen (murine mammary tumor virus-polyoma middle T-antigen)-induced breast cancer, this study revealed that a loss of KISS1R attenuated breast tumor initiation, growth, and metastasis compared with the polyoma middle T-antigen/ Kiss1r ϩ/ϩ mice (30). Additionally, KISS1R was depleted in H-RasV12-transformed MCF10A cells, a nonmalignant human mammary epithelial cell model that endogenously expresses KISS1R.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The PCR product was cloned into the lentiviral vector pLVX-IRESZsGreen1. The constitutively active mutants of RhoA, Rac1, and Gq were cloned as previously described (21). Full-length RGS2 and the RGS domain of p115RhoGEF (including amino acid residues 1-252) were amplified by PCR and cloned into the EcoR1/BamH1 site of p3ÂFLAG-CMVÔ-10.…”
Section: Plasmid Constructsmentioning
confidence: 99%
“…A recent landmark study established a role for KP/KISS1R signaling in regulating breast cancer metastasis using a mouse mammary tumor virus-polyoma virus middle T antigen (MMTV-PyMT) model63. In this model, the transformation of the mammary epithelium leads to the development of multifocal mammary adenocarcinomas and metastatic lesions in the lymph nodes and in the lungs.…”
Section: Kp/kiss1r Signaling In Breast Cancer Metastasismentioning
confidence: 99%